Criminal Liability for Extremist Crimes Through Electronic Means in Modern Legislation : a Comparative Study - Haider Kazim Hattahut (International Journal of Law and Society, 2025)
The aim of this comparative study is to identify the criminal responsibility for extremism through electronic means in modern legislation for which the researcher used the comparative analytical method. The research problem is centred on the statement of the objective provisions of criminal responsibility for the crime of extremism through electronic means in both Iraqi law and comparative laws. The study relied on a number of primary and secondary references both past and present to collect legal information. The study concluded a number of the most important results, namely that extremism using electronic means is the aggression emanating from pirates using electronic means with the aim of disrupting security and public order and extorting the authorities by seizing public and private funds and damaging property. Results also show that the competent court in considering the crime of extremism using electronic means is the State Security Court in Iraqi law, and we see the Iraqi legislator in the Iraqi Constitution of 2005 was unique in reducing the penalty until amnesty for those who provide information about cyber attacks. The study recommended that there should be a clear text for the crime to define the electronic means as per the Iraqi legislator, while the modern legislations came in conjunction and close to the Jordanian legislator, as well as the French law, the Algerian and Egyptian legislator. The study also recommends that the Iraqi legislator follow the example of the Jordanian legislator in issuing a special law for electronic crimes and contain the text of criminalising the crime of cyber extremism. The study also stresses the need for judges to have sufficient knowledge of electronic means and the Internet in order to consider cases in this regard by preparing courses for them and all those working in the field of combating cyber extremism crimes. This is particularly true since the threat is carried out through the Internet and electronic means.